THE CONNECTION BETWEEN INTRAPERSONAL CONFLICT AND IDENTITY CRISIS IN ADOLESCENCE - Демченко, Наталія; Кошель, Карина (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article presents the results of a theoretical and empirical study on the psychological features of intrapersonal conflicts in youth. The relevance of the work is driven by the fact that under the conditions of modern social transformations, war, and instability in Ukraine, the process of self-determination among young people is significantly complicated, taking on the characteristics of an acute existential contradiction. Internal conflict is viewed by the authors not only as a source of tension but also as a mechanism of personal growth closely linked to the formation of ego-identity. The aim of the article is to identify the nature of the relationship between identity statuses and the specifics of intrapersonal conflicts, self-attitude, and life-meaning orientations of students. The empirical study was conducted on a sample of 60 respondents using a psychodiagnostic complex: J. Marcia’s Ego Identity Status measure, the Self-Attitude Test, and the Purpose-in-Life Test. Statistical data processing was performed using the Shapiro-Wilk normality test and Pearson correlation coefficient. The research results showed that the dominant status in the sample is "Achieved Identity" (56%). This fact is interpreted as a specific adaptive response of youth to crisis conditions: the need for rapid maturation and building internal supports reduces the time for "moratorium" (search), which accounted for only 15%. Correlation analysis allowed establishing that identity status directly determines the content of the internal conflict. It was revealed that "Identity Diffusion" has significant negative correlations with self-respect and life goals against the background of a positive correlation with self-blame, indicating the experience of conflict as a state of disorientation. The "Moratorium" status is accompanied by a high level of self-criticism, reflecting conflict as an active search. The phenomenon of "latent conflict" was recorded in individuals with "Foreclosure," manifested through a link with self-blame despite external stability. In contrast, "Achieved Identity" has stable positive correlations with autosympathy and life meaningfulness. It is concluded that the successful resolution of the identity crisis transforms the destructive potential of internal conflict into a development resource, ensuring the psychological resilience and agency of the personality.